In‐Cage Interactions in the Clathrate Superconductor Sr8Si46. Issue 4 (12th December 2019) - Hübner, Julia‐Maria; Prots, Yurii; Schnelle, Walter; Bobnar, Matej; König, Markus; Baitinger, Michael; Simon, Paul; Carrillo‐Cabrera, Wilder; Ormeci, Alim; Svanidze, Eteri; Grin, Yuri; Schwarz, Ulrich
Abstract: The clathrate I superconductor Sr8 Si46 is obtained under high‐pressure high‐temperature conditions, at 5 GPa and temperatures in the range of 1273 to 1373 K. At ambient pressure, the compound decomposes upon heating at T= 796(5) K into Si and SrSi2 . The crystal structure of the clathrate is isotypic to that of Na8 Si46 . Chemical bonding analysis reveals conventional covalent bonding within the silicon network as well as additional multi‐atomic interactions between Sr and Si within the framework cages. Physical measurements indicate a bulk BCS type II superconducting state below T c =3.8(3) K. Abstract : Clathrate I Sr8 Si46 is obtained at high‐pressure high‐temperature conditions. Conventional covalent bonding within the silicon network goes along with additional multi‐atomic inter‐actions between Sr and Si in the framework cages. The compound is a bulk BCS type II superconductor below T c =3.8(3) K.